Landslides induced by the 2023 Jishishan Ms6.2 earthquake (NW China): spatial distribution characteristics and implication for the seismogenic fault - Yuandong Huang; Chong Xu; Xiangli He; Jia Cheng; Xiwei Xu; Yingying Tian (npj Natural Hazards)
Abstract This study provides a detailed interpretation of 2643 landslides triggered by the 2023 Ms6.0 Jishishan earthquake using remote sensing imagery and GIS analysis. The landslides’ spatial distribution, scale, and relationships with environmental factors were investigated. Findings show a concentration of landslides in the eastern hilly and plain areas, primarily under 1000 m2. Significant factors include elevations of 1700–2300 m, slope angle of 20–40°, southeast and south aspects, middle slope positions, Paleogene and Neogene strata, and proximity within 400 m of rivers, with NDVI values of 0.2–0.6 and PGA of 0.45–0.6 g. Our analysis indicates an NE-dipping thrust fault with a distinct “hanging wall effect”. These results contribute to the coseismic landslide database for Northwest China, advance the understanding of influencing factors, support seismogenic fault identification, and hold significance for improving risk assessment and emergency response capabilities.